Enhanced efficiency fertilizers: Overview of production methods, materials used, nutrients release mechanisms, benefits and considerations - Christian O. Asadu; Chinonso Anthony Ezema; Benjamin Nnamdi Ekwueme; Chijioke Elijah Onu; Ikechukwu Maxwell Onoh; Thomas Adejoh; Timothy Prince Chidike Ezeorba; Churchill Chisom Ogbonna; Patricia Ihuaku Otuh; Japheth O. Okoye; Umeagukwu O. Emmanuel (Environmental Pollution and Management)
The application of fertilizers is necessary for continuous replenishment of plants nutrients, sustaining the productivity of soils. Inorganic fertilizers are very simple, chemically defined, water soluble, and easily absorbed for immediate and reproducible responses in plants. In excess of plants needs however, they do not only scorch plants, but are also lost to the atmosphere as greenhouse gases. Prolonged usage leads to reduced soil quality, soil acidification (accompanied by dissolution of soil carbonate and greenhouse gases emission), and contamination of underground water. Increasing nutrients use efficiency ameliorates these problems by ensuring a better synchronization of nutrients availability with nutrients uptake. Without increasing the frequency of fertilization and the associated labor cost (encountered in split-fertilization), enhanced efficiency fertilizers (EEFs) gradually make nutrients available over a long period of time, ensuring that plants needs are met after a single seasonal fertilization, without compromising the integrity of soil. EEFs do not only benefits the environment by retarding nutrients availability; some of the materials used in EEFs formulation also impact beneficial qualities (e.g., improved soil structure, and reduced erosion) to soil. The production of EEFs, such as coated fertilizers, depending on the nature of the coat, are not completely environmentally and cost friendly; and the effects of certain EEFs are not easily reproducible due to variability between fertilizer batches and soil conditions. These challenges in development and application of different EEFs, and potential solutions, materials used in their formulation, in addition to the advantages of their usage are discussed. The information contained herein are expected to arouse more research in sustainable development of EEFs and assist farmers in selecting the best kind of fertilizers, depending on the plants and soil condition, for improved crops production, while sustaining soil health.